E–RECOVERY SERVICE QUALITY TERHADAP E-LOYALTY PELANGGAN GOFOOD BANDUNG - Dita Amanah; Dedy Ansari Harahap (Niagawan, 2023)
It is necessary to know the application of E-Recovery Service Quality to understand E-Loyalty for Gojek customers, GoFood Features. Loyal customers or regular customers, will make the business continue to survive because loyal customers feel comfortable with certain products, so they will repeatedly make purchases.The survey method is the method used in this study and the sampling technique is purposive sampling. This type of research is descriptive and quantitative verification. The population in this study were Gojek GoFood Feature customers in the city of Bandung with a sample size of 100 respondents. The data analysis method used is simple linear analysis to analyze the effect of E-Recovery Service Quality on E-Loyalty.The test results show that E-Recovery Service Quality has a significant effect on E-Loyalty for Gojek GoFood Feature customers with a t value of 8.149. Value of t table < t count or 1.966 < 8.149 with a significance value < 0.05, namely 0.000 < 0.05.The beta coefficient value is 0.546, which means that E-Recovery Service Quality can explain E-Loyalty of 54.60% or states that every change of one unit of E-Recovery Service Quality can result in a change in E-Loyalty of 54.60%. The discussion and recommendations given are all written in this article.